Three‐dimensional Transesophageal images of a pulmonary autograft in the mitral position (Ross II Procedure) in an adult. Issue 5 (15th April 2020) - Haddy, Steven
Abstract: Few images are available in the literature of the Ross II procedure wherein the pulmonary valve is autotransplanted into the mitral position. These images are from a 33‐year‐old woman who underwent the procedure 18 years ago.